Attention deficit hyperactivity disorder and risk of migraine: A nationwide longitudinal study. Issue 5 (6th May 2022) - Hsu, Tien‐Wei; Chen, Mu‐Hong; Chu, Che‐Sheng; Tsai, Shih‐Jen; Bai, Ya‐Mei; Su, Tung‐Ping; Chen, Tzeng‐Ji; Liang, Chih‐Sung
Abstract: Objective: This study explored the risk of migraine in children, adolescents, and young adults with attention deficit hyperactivity disorder (ADHD) and its association with ADHD medications. Background: The prevalence of migraine peaks between the ages of 35 and 39 years. Recent studies have reported a positive association between ADHD and migraine. Methods: This longitudinal case‐cohort study was conducted using data from the Taiwan National Health Insurance Database. Between 2001 and 2009, we enrolled 81, 441 participants with ADHD and a 1:1‐matched control cohort for age, sex, and physical and psychiatric comorbidities. All participants had no diagnosis of migraine before enrollment and were followed up to the end of 2011. We examined the risk of newly diagnosed migraine among patients with ADHD and matched controls after adjusting for demographics and physical/psychiatric comorbidities. Results: Patients with ADHD had a higher incidence of migraine than those in the control group (462/81441 [0.6%] vs. 212/81441 [0.3%] patients, p  < 0.001). After adjusting for potential confounders, the hazard ratio (HR) was 1.92 (95% CI, 1.64–2.34) for migraine in patients with ADHD versus controls. The subgroup analyses stratified by age showed the HRs were 2.01 (95% CI, 1.63–2.49), 1.94 (95% CI, 1.35–2.79), and 1.31 (95% CI, 0.58–2.98) for children (<12 years old), adolescents (12–17), and young adults (18–29), respectively, versus controls. When stratified by sex, the HR was 1.97 (95% CI, 1.58–2.46) for men and 1.94 (95% CI, 1.44–2.62) for women versus controls. The cumulative daily dose of ADHD medications was not associated with the risk of migraine. Conclusion: Children and adolescents with ADHD were associated with an increased risk of migraine compared with matched controls. The increased risk was not observed in young adults with ADHD. Further studies are required to examine the mechanisms between migraine and ADHD.